EFISIENSI PENGGUNAAN ALAT BERAT PADA PEKERJAAN PEMBANGUNAN TPA (TEMPAT PEMPROSESAN AKHIR ) DESA AMD KEC. MUARA BULIAN KAB. BATANGHARI - Elvira Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Heavy equipment is a unity that can not be separated in the work of development of infrastructure. Heavy equipment is more profitable than using manual tools because it can get the job done faster development, so the timing of the work can be achieved with the construction optimal.Pekerjaan landfill (final processing) is one job that requires heavy equipment production capacity optimal, because the The job has a job excavation, pile and transport of large volumes, Based on theoretical calculations and analysis in the field, the conclusion that can be drawn from this study are as follows: Difference in production capacity and the efficiency factor of heavy equipment as follows:a. Difference in Production Capacity : Excavator: 56.93 m3 / hour of the analysis in the field, Bulldozer: 7571.92 m2 / h greater theoretically, Vibrator Roller: 1826.67 m3 / h greater theoretically. b. Difference Factor Efficiency : Excavator: 0,003, Bulldozer: 0 (same), Vibrator Roller: 0.011keyword : heavy equipment, construction